IMPLEMENTASI PROGRAM KB DI KABUPATEN GUNUNG KIDUL PADA ERA DESENTRALISASI - , Leksi Goeslaw, SIP ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is background for program implementation in Gunung Kidul regency. This research is  destinied  to  know  the  Family  Planning  program  implementation  in  Gunung  Kidul  regency  and  the factors which influence the Family Planning  implementation program in Gunung Kidul regency. Research  method  was  used  is  descriptive  research.  Research  sample  is  the  officer  of  Family Planning  and   the  acceptor  of  Family  Planning.  The  data  is  gathered  through  observation, questionnaire, interview and documentation studied. This interview is addressed to employee Agency of empowerment women, Society and Family Planning (BPPM and KB), the officer of PLKB and the society. The data was analyzed by descriptive analysis technique. The  result  of  research  was  showed  that  is